Hydrophobic peptide auxotrophy in Salmonella typhimurium. - Brãnes, L V (1981)
The growth of a pleiotropic membrane mutant of Salmonella typhimurium with modified lipopolysaccharide composition was found to be strictly dependent on the peptone component of complex media. Nutritional Shiftdown into minimal media allowed growth for three to four generations. Of 20 commercial peptones, only enzymatic digests supported growth to varying degrees. Neither trace cations, amino acids, vitamins, carbohydrates, lipids, glutathione, polyamines, carbodimides, nor synthetic peptides stimulated growth; however, cells still metabolized carbohydrates, and amino acid transport systems were shown to be functional. A tryptic digest of casein was fractionated into four electrophoretically different peptide fractions of 1,000 to 1,200 molecular weight which supported growth to varying degrees. The best of these was further fractionated to two highly hydrophopic peptides. N-terminal modifications eliminated biological activity. Fluorescein-conjugated goat antibody to rabbit immunoglobulin G was used as a probe to detect antipeptide antibody-peptide complexes on membrane preparations. Cells grown on peptone distributed the peptide into both inner and outer membranes. The peptide could be removed with chaotropic agents, and cells had to be pregrown in peptone-containing media to bind the hydrophobic peptide. The gene (hyp) responsible for peptide auxotrophy was mapped at 44 to 45 units by conjugation.